Certain Bound for q-Starlike and q-Convex Functions with respect to Symmetric Points. (29th October 2015) - Ramachandran, C.; Kavitha, D.; Soupramanien, T.
Abstract : The aim of this paper is to establish the coefficient estimates for the subclasses of q -starlike and q -convex functions with respect to symmetric points involving q -difference operator. Also certain applications based on these results for subclasses of univalent functions defined by convolution are given.